Is the international business environment the actual context of IB research? - Ferreira, Manuel Portugal (2009)
The International Business Environment (IBE) is argued to be the essential context for international business (IB) studies and the distinguishing factor from other management studies, and from studies of large scale enterprises. In this paper we argue for a greater environmental focus and illustrate how and how much the IBE has been included in published IB research. While extant research has often taken a uni-dimensional view, which has been mostly anchored in the cultural environment, we suggest that: (a) there is a need to developed more uni-and multi-dimensional environmental constructs, (b) a more holistic view of the IBE provides richer insights on the actual complexity that underlies IB research. Future conceptual and empirical studies that provide more comprehensive models of the IBE that overcome the usual "everything out there" are warranted.